Ensemble Interval Prediction for Solar Photovoltaic Power Generation - Yaxin Zhang; Tao Hu (Energies, 2022)
In recent years, solar photovoltaic power generation has emerged as an essential means of energy supply. The prediction of its active power is not only conducive to cost saving but can also promote the development of solar power generation industry. However, it is challenging to obtain an accurate and high-quality interval prediction of active power. Based on the data set of desert knowledge in the Australia solar center in Australia, firstly, we have compared twelve interval prediction methods based on machine learning. Secondly, six ensemble methods, namely Ensemble-Mean, Ensemble-Median (Ensemble-Med), Ensemble-Envelop (Ensemble-En), Ensemble-Probability averaging of endpoints and simple averaging of midpoints (Ensemble-PM), Ensemble-Exterior trimming (Ensemble-TE), and Ensemble-Interior trimming (Ensemble-TI) are used to combine forecast intervals. The result indicates that Ensemble-TE is the best method. Additionally, compared to other methods, Ensemble-TE ensures the prediction interval coverage probability for confidence levels of 95%, 90%, 85%, and 80% as 0.960, 0.920, 0.873, and 0.824, respectively, using 15-min level data. Meanwhile, the narrower prediction interval normalized averaged width is calculated for the same confidence levels as 0.066, 0.045, 0.035, and 0.028, respectively. In addition, higher Winkler score and smaller coverage width-based criterion are obtained, representing high-quality intervals. We have calculated smaller mean prediction interval center deviation, which is approximately 0.044. Thus, the above demonstrates that this study obtains the prediction interval with better performance compared to other existing methods.